Pleurotus ostreatus cultivation : physico-chemical characteristics of a robust pre-blocks oyster mushroom substrate with absorptive starch binders - Saiful Irwan Zubairi,; Nur Arif Syamimi Md Zabidi,; Zoey Zeffrey Azman,; Siti Noor Diana Mohd Kamaruddin,; Zalifah Mohd Kasim,; Azwan Mat Lazim,; Zainun Nurzahim,; Mohd Suzeren Md Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2022)
An alternative way of preparing a newly robust and low fragility of the Pleurotus ostreatus (oyster mushroom) cultivation media is needed as this major problem occurred during harvesting and recyclability. Thus, the cultivation of P. ostreatus mushroom in the form of robust blocks bound together with starch using different tapioca flour binder concentration of 5%, 10% and 25% (w/v) was evaluated for cultivation method development. How mushroom block binder material affects the biological efficiency (BE) and its vegetative growth on newly robust media were identified. The optimized composition of the conventional mushroom substrate has been prepared as a benchmark with the ratio of 100: 10: 1 to residual sawdust, agricultural rice bran and agricultural lime prior to binder mixing. Mushroom BE from bag cultivation methods had been used as a control, which produced lower BE (13%, w/w) than the blocks with a binder (ranging from 18 to 29%, w/w) (p<0.05). The mushroom block with a concentration of 25% (w/v) tapioca flour was found to have a higher bulk density with an average value of 0.87 g/cm3 as compared to the mushroom blocks of 10% (w/v) and 5% (w/v) tapioca flour (p<0.05). The highest water absorption was obtained in the block with 5% (w/v) tapioca flour with a value of 300.18% (w/w) on a dry basis. In terms of compressive strength, the substrate of the mushroom block from 25% (w/v) tapioca flour had the highest value with 0.022 N/mm2. The pH value of the substrate before seeding was between 8 and 9 whereas post-seeding value was measured at 4 to 6. The physico-chemical analysis of density, water absorption, compressive strength test, pH and colour values exhibited a good and ideal micro-environment growth of the mushroom. Some nutritional deficiencies in the pre-blocks were observed through imperatively acceptable as compared to the compressed substrate in polypropylene bags (PP). The pre-block formulations with 5% (w/v) and 25% (w/v) tapioca flour conceive good potential and potency in producing high BE of P. ostreatus without compromising its nutritional health benefits.